Incidence of childhood type 1 diabetes mellitus in Ireland remains high but no longer rising. (18th March 2021) - McKenna, Amanda; O'Regan, Myra; Ryder, Kerry; Fitzgerald, Helen; Hoey, Hilary; Roche, Edna
Abstract: Aim: The global incidence of type 1 diabetes mellitus (T1DM) varies considerably geographically. Ireland has a high incidence of T1DM. Incidence accelerated between 1997 and 2008, although more recent data (2008–2013) suggested stabilisation in the incidence rate (IR). This study sought to determine IRs for 2014 to 2018. Methods: Incident cases were prospectively recorded through the established Irish Childhood Diabetes National Register (ICDNR). Cases were verified, and IRs were calculated. Capture‐recapture methodology was identical to previous studies. Age and seasonality data were compared. Results: A total of 1429 cases were reported (age range 0.45–14.98 years), with significantly more males (772, 54%) and male‐to‐female ratio of 1.17 (95% CI 1.05, 1.29). Standardised IRs for T1DM in the period were 28.0; 29.6; 30.9; 27.0; and 27.1/100, 000/year, respectively. There was a slight reduction in standardised IR, more marked in females than males (9.9% v 1.6%). The highest IR remains in the 10‐ to 14‐year‐old age group (44% of total cases). Seasonality of diagnosis is persistently higher in autumn and winter. Conclusion: Ireland remains a high incidence country, despite a minor reduction in incidence rates. Ongoing incidence monitoring through national registers is vital to inform healthcare services, research relating to aetiology and paediatric diabetes management.